Cytokine profiles in Malawian children presenting with uncomplicated malaria, severe malarial anemia and cerebral malaria. - Mandala, W; Msefula, C; Gondwe, E; Drayson, M; Molyneux, M; MacLennan, C (American Society for Microbiology, 2017)
Pro-inflammatory cytokines are involved in clearance of Plasmodium falciparum, and very high levels of these cytokines have been implicated in the pathogenesis of severe malaria. In order to determine how cytokines vary with disease severity and syndrome, we enrolled Malawian children presenting with cerebral malaria (CM), severe malarial anaemia (SMA) and uncomplicated malaria (UCM), and healthy controls. We analysed serum cytokine concentrations in acute infection, and in convalescence. With the exception of IL-5, cytokine concentrations were highest in acute CM, followed by SMA, and were only mildly elevated in UCM. Cytokine concentrations had fallen to control levels when re-measured at one month of convalescence in all three clinical malaria groups. IL-10-to-TNF-α and IL-10-to-IL-6 ratios followed a similar pattern. Compared to concentrations in sera from healthy controls, children presenting with acute CM had significantly higher concentrations of TNF-α (p<0.0001), IFN-γ (p=0.0019), IL-2 (p=0.0004), IL-6 (p<0.0001), IL-8 (p<0.0001) and IL-10 (p<0.0001). Compared to those presenting with acute SMA, acute CM patients had significantly higher concentrations of IL-6 (p<0.0001) and IL-10 (p=0.0003). Our findings are consistent with the concept that high levels of pro-inflammatory cytokines, despite high levels of the anti-inflammatory cytokine IL-10, could contribute to the pathogenesis of CM.